2017
DOI: 10.1007/s00127-017-1412-y
|View full text |Cite
|
Sign up to set email alerts
|

Individual-level exposure to disaster, neighborhood environmental characteristics, and their independent and combined associations with depressive symptoms in women

Abstract: Purpose The severity of the stress response to experiencing disaster depends on individual exposure and background stress prior to the event. To date, there is limited research on the interaction between neighborhood environmental stress and experiencing an oil spill, and their effects on depression. The objective of the current study was to assess if the association between exposure to the Deepwater Horizon Oil Spill (DHOS) and depressive symptoms varied by neighborhood characteristics. Methods U.S. Census … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Previous investigations from this sample suggested that increased oil spill exposure (physical and economic) was significantly associated with depression symptoms over time (S. A. Gaston et al, 2017;Rung et al, 2016;Rung et al, 2018). This pattern of findings is consistent with a rich literature suggesting that PTSD and depressed mood frequently co-occur and have shared risk factors (Campbell et al, 2007;Goldstein et al, 2016;Spinhoven, Penninx, van Hemert, de Rooij, & Elzinga, 2014;Wisco et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Previous investigations from this sample suggested that increased oil spill exposure (physical and economic) was significantly associated with depression symptoms over time (S. A. Gaston et al, 2017;Rung et al, 2016;Rung et al, 2018). This pattern of findings is consistent with a rich literature suggesting that PTSD and depressed mood frequently co-occur and have shared risk factors (Campbell et al, 2007;Goldstein et al, 2016;Spinhoven, Penninx, van Hemert, de Rooij, & Elzinga, 2014;Wisco et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…SES aspects of the neighborhood, racial composition, physical and social environment, and segregation are all neighborhood and contextual factors that have mental health implications [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Ethnic density is one of the major factors that shapes PRD and depression for minorities including Blacks [ 49 , 54 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, results across a range of other, more targeted studies indicate increased reports from individuals of symptoms consistent with depression, anxiety, and post-traumatic stress (Grattan et al, 2011;H.J. Osofsky et al, , 2015Buttke et al, 2012a,b;Gill et al 2012Gill et al , 2014Morris et al, 2013;Drescher et al, 2014;Cherry et al, 2015;Fan et al, 2015;Aiena et al, 2016;Rung et al, 2016, Gaston et al, 2017Kwok et al, 2017b). Substantial portions of coastal households (e.g., nearly 38% of an Alabama sample; Ritchie et al, 2018) were involved directly or indirectly in DWH-related claims, settlements, or litigation activity.…”
Section: Health Effects On Non-workersmentioning
confidence: 99%